Analysis of co-firing palm oil waste for the economic and emission performance of PLTU in Riau - Aulia Ramadhan; Anita Susilawati; Asral; Dodi Sofyan Arief; Dinni Agustina (BKS-TM Indonesia, 2025)
This study evaluates the co-firing of palm oil industry waste biomass, specifically Palm Kernel Shell (PKS) and Empty Fruit Bunch (EFB) pellets, in coal-fired power plants (PLTU) in Riau, Indonesia, to support a sustainable energy transition. Empirical tests were conducted at PLTU Tenayan and Tembilahan, using biomass substitution rates of 5% and 50%, respectively. Key performance indicators, including Specific Fuel Consumption (SFC), Net Plant Heat Rate (NPHR), production cost, and exhaust emissions (SO₂ and NOₓ), were analyzed. Results show that 5% PKS co-firing at PLTU Tenayan reduced SFC from 0.871 to 0.856 kg/kWh and NPHR from 4,187 to 4,116 kCal/kWh, while 50% PKS co-firing at PLTU Tembilahan decreased SFC from 1.171 to 0.785 kg/kWh and NPHR from 5,312 to 3,625 kCal/kWh. Economically, PKS co-firing resulted in cost savings of up to Rp223.58/kWh. Emission measurements revealed SO₂ reductions up to 27.8% at PLTU Tenayan and 34% at PLTU Tembilahan (EFB scenario), with NOₓ emissions remaining stable or decreasing by up to 13%. Conversely, EFB pellet co-firing increased fuel consumption and production costs due to higher fuel prices and operational challenges. The study confirms that PKS co-firing is a viable and effective approach to enhance power plant efficiency, reduce emissions, and lower costs in palm oil-producing regions. Limitations include short test durations and limited plant sites; therefore, long-term monitoring is recommended to assess boiler integrity, operational stability, and emission performance for sustainable large-scale implementation. This research provides critical technical, economic, and environmental insights for advancing biomass co-firing in commercial coal power plants.